2013
DOI: 10.1021/la304046q
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Role of Molybdenum in the Electrochemical Deposition of Biological Macromolecules on Metallic Surfaces

Abstract: The corrosion of CoCrMo, an alloy frequently used in orthopedic implants, was studied with an electrochemical quartz crystal microbalance (QCM) in three physiologically relevant solutions. Mass changes were measured during potentiodynamic tests, showing material deposition in protein solutions at potential levels that caused mass loss when the proteins were not present. X-ray photoelectron spectroscopy (XPS) data indicated that the deposited material was primarily organic and therefore was most likely derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 42 publications
1
47
0
Order By: Relevance
“…In the transpassive potential, protein adsorption on an oxide film was also observed [79]. At this transpassive potential, the dissolution of Mo(VI) ions may additionally promote protein deposition [81]. Although the bilayer tribofilm is compatible with both a passive and transpassive state of the alloy, transpassive potentials require the presence of strong oxidising agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the transpassive potential, protein adsorption on an oxide film was also observed [79]. At this transpassive potential, the dissolution of Mo(VI) ions may additionally promote protein deposition [81]. Although the bilayer tribofilm is compatible with both a passive and transpassive state of the alloy, transpassive potentials require the presence of strong oxidising agents.…”
Section: Discussionmentioning
confidence: 99%
“…Those oxidising agents can be present in the synovial fluid due to inflammatory cell processes in the surrounding tissues [101] or can be in principle be generated locally at contact spots undergoing high temperatures. In the former case, based on mechanisms proposed by Martin et al [81], one would expect a reaction film that covers the whole surface, while in the latter case, the tribofilm would form in the localized contact zone only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of our own studies concluded that the occurrence of proteins directly affects the synergism of wear and corrosion in the tribocontact [32]. The release of molybdenum(VI)-ions during tribocorrosion might be responsible for the formation of a proteinaceous layer on the surface [33], which then undergoes mechanical mixing under the applied tribological stresses to form a tribofilm [34,35]. The results of this study suggest that the presence of a tribofilm diminishes the load sensitivity of wear and leads to a constant rate of material loss over a substantial range of applied contact stress.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin influences the corrosion process of CoCrMo by enhancing passive [4,5] and transpassive dissolution [6] as well as modifying surface chemistry [5,7]. Wear of these alloys is also highly dependent on the presence of Albumin [8] in the electrolyte, which can affect the corrosion response to friction as well as the mechanical mechanisms leading to wear.…”
Section: Introductionmentioning
confidence: 99%